Infection with Helicobacter pylori is associated with protection against tuberculosis. - Sharon Perry; Bouke C de Jong; Jay V Solnick; Maria de la Luz Sanchez; Shufang Yang; Philana Ling Lin; Lori M Hansen; Najeeha Talat; Philip C Hill; Rabia Hussain; Richard A Adegbola; Joanne Flynn; et al. (PLoS ONE)
Background Helicobacter pylori, a lifelong and typically asymptomatic infection of the stomach, profoundly alters gastric immune responses, and may benefit the host in protection against other pathogens. We explored the hypothesis that H. pylori contributes to the control of infection with Mycobacterium tuberculosis. Methodology/principal findings We first examined M. tuberculosis-specific IFN-gamma and H. pylori antibody responses in 339 healthy Northern Californians undergoing routine tuberculin skin testing. Of 97 subjects (29%) meeting criteria for latent tuberculosis (TB) infection (LTBI), 45 (46%) were H. pylori seropositive. Subjects with LTBI who were H. pylori-seropositive had 1.5-fold higher TB antigen-induced IFN-gamma responses (p = 0.04, ANOVA), and a more Th-1 like cytokine profile in peripheral blood mononuclear cells, compared to those who were H. pylori seronegative. To explore an association between H. pylori infection and clinical outcome of TB exposure, we evaluated H. pylori seroprevalence in baseline samples from two high risk TB case-contact cohorts, and from cynomolgus macaques experimentally challenged with M. tuberculosis. Compared to 513 household contacts who did not progress to active disease during a median 24 months follow-up, 120 prevalent TB cases were significantly less likely to be H. pylori infected (AOR: 0.55, 95% CI 0.0.36-0.83, p = 0.005), though seroprevalence was not significantly different from non-progressors in 37 incident TB cases (AOR: 1.35 [95% CI 0.63-2.9] p = 0.44). Cynomolgus macaques with natural H. pylori infection were significantly less likely to progress to TB 6 to 8 months after M. tuberculosis challenge (RR: 0.31 [95% CI 0.12-0.80], p = 0.04). Conclusions/significance H. pylori infection may induce bystander effects that modify the risk of active TB in humans and non-human primates. That immunity to TB may be enhanced by exposure to other microbial agents may have important implications for vaccine development and disease control.